The Relationship of Energy Generation from Fossil Fuels, Low Carbon Resources, and Renewable Resources and Inflation within the Framework of Taylor’s Rule: The Case of Kazakhstan - Niyetalina, Gaukhar; Balapanova, Elmira; Kuralbayev, Almas; Lukhmanova, Gulnar; Bolganbayev, Artur (International Journal of Energy Economics and Policy, 2023)
This study analyzes the relationship between energy production from fossil fuels, low-carbon sources, and renewable sources and inflation in Kazakhstan from 2000 to 2021, using the VAR method within the framework of the Taylor rule. Energy production is categorized under two headings, namely from fossil fuels and from other sources. While examining the relationship between energy production from fossil fuels and inflation, the interest rate and GDP growth rate, which affect inflation, were also included in the model as control variables following Taylor’s rule. Thus, the relationship between energy production from fossil fuels and inflation can be analyzed more realistically. Energy production data are obtained from Our World in Data, GDP data from the World Bank site, and interest and inflation data from the ADB Data Library. The study showed that the interest rate affects inflation following the Taylor rule. We found a significant relationship between energy production and inflation in Kazakhstan. The relationship is that energy production from fossil sources increases inflation, while energy production from other (renewable and low-carbon) sources reduces inflation. This result once again proved the importance of energy production from renewable and low-carbon sources for Kazakhstan. Furthermore, the relationship between inflation and energy production proved not to be a causal one.